Insuring against drought-related livestock mortality: Piloting index-based livestock insurance in northern Kenya - Mude, Andrew G.; Chantarat, S.; Barrett, Christopher B.; Carter, M.; Ikegami, Munenobu; McPeak, J.G. (Alliance for a Green Revolution in Africa and International Livestock Research Institute, 2011)
Climate related shocks are among the leading cause of production and efficiency losses in smallholder crop and livestock production in rural Africa. Consequently, the identification of tools to help manage the risks associated with climactic extremities is increasingly considered to be among the key pillars of any agenda to enhance agricultural growth and welfare in rural Africa. This paper describes the application of a promising innovation in insurance design – index-based insurance – that seeks to bring the benefits of formal insurance to help manage the weather-related risks faced by rural crop and livestock producers in low-income countries. In particular, we highlight the research and development agenda of a comprehensive effort to design commercially viable index based livestock insurance aimed at protecting the pastoral populations of northern Kenya from the considerable drought-related livestock mortality risk that they face. Detailing the conditions that make the pastoral economy in northern Kenya an ideal candidate for the provision of indexbased insurance products, the paper describes the contract design, defines its structure, offers analysis that indicates a high likelihood of commercial sustainability among the target market and describes the process of implementation leading up to the launch of a pilot in Marsabit District of northern Kenya in early 2010.